Evaluating pre-anesthesia assessment performance in residency: the reliability of standardized patient methods - Besnier, Emmanuel; Franchina, Sébastien; Lefevre-Scelles, Antoine; Wable, Thierry; Hanouz, Jean-Luc; Allard, Etienne; Dureuil, Bertrand; Compère, Vincent (Frontiers in Medicine, 2024)
Background Pre-anesthesia assessment clinic (PAC) is known to increase safety and quality in the perioperative period. However, PAC teaching during anesthesiology residency is a challenge. The objective of this study was to assess the reliability of a simulation score grid using a standardized patient on the PAC performance of anesthesiology residents. Methods A score grid, including the 4 components of the PAC (clinical evaluation, perioperative strategy, information and communication) was validated by a group of 5 senior anesthesiologists. Anesthesiology residents (> one year) and attending anesthesiologists were included. The same simulation sequence with the same standardized patient was conducted in a simulation dedicated consultation room. The simulation sequence was followed by a debriefing session with the 2 professors (anesthesiology and communication) and each anesthesiology resident. The main outcome was the overall grid score out of a maximum score of 300 and the correlation of this score with experience in anesthesiology residency. Secondary outcomes were individual component scores according to level of experience in anesthesiology. Results Between October 2014 and April 2016, 109 anesthesiology residents and 16 attending anesthesiologists were included in this prospective bicentric study. There was a positive correlation (p < 0.01) between level of experience and overall score on the grid score (Pearson’s Coefficient = 0.52). The Pearson correlation coefficient between overall assessment and level of experience in anesthesiology was 0.46 (p < 0.01). The analysis of the sub-scores for the 4 components of the overall score (evaluation, perioperative strategy, information and communication) also identify differences between groups of experience. Conclusion Standardized patient Simulation of PAC seems to be a reliable tool to assess PAC performance in anesthesiology residents and senior anesthesiologists. These results suggest standardized patient simulation could be used as a teaching tool for PAC.